PERSONNEL MANAGEMENT PRACTICES IN NIGERIAN QUANTITY SURVEYING FIRMS - Ayodeji OKE; Clinton AIGBAVBOA; Wellington THWALA (Journal of Construction Project Management and Innovation)
One of the basic responsibilities of top managers of an organisation is the ability to manage, supervise and control other members of staff in the best possible way to ensure optimum performance and high productivity. Failure to understand, acknowledge and meet the expectation and requirement of staff members by an organisation may lead to deterioration in commitment, loyalty to the values of the organisation, lack of motivation and eventually, low productivity. In this study, personnel management (PM) practices in Nigerian quantity surveying firms were examined by evaluating various human resource management (HRM) approach and techniques. The aspects considered are staff strength, welfare, training and development, mentoring and succession rate. Questionnaires were adopted for the study and it was administered on quantity surveying firms using convenient sampling method. Quantity surveying firms are not providing their members of staff with the necessary and expected welfare and mentoring and level of staff training is below average. In view of this, managers, directors and other top management staff of quantity surveying firms should ensure proper recruitment and selection process at the initial stage of personnel management; improve on staff training and development strategies; be concerned about staff welfare and mentoring; maintain a strong, stable, and increasing staff strength; and prioritise staff mentoring and succession in order to enhance productivity of staff and general performance of the firms. This will not only improve their innovativeness in delivering better to clients but will also enhance better competition in both local and international market.